IDO1-AhR axis increases T regulatory cells in Plasmodium vivax malaria infection - Santos, Rafaella Oliveira dos; Carvalho, Nani Oliveira; Morais, Thiago Barros do Nascimento de; Sobrinho, Wlademir Braga Salgado; Cruz, Maria Geuziane Soares da; Faria, Elaine Speziali de; de Araújo, Fernanda Fortes; Magalhães, Vanessa Peruhype; Lopes, Stefanie Costa Pinto; Malheiros, Adriana; Mota, Adolfo José da; Santiago, Helton da Costa; et al. (Frontiers in Immunology, 2025)
IntroductionMalaria remains a significant public health challenge in Brazil, where Plasmodium vivax (P. vivax) is the predominant species. Dysregulated immune responses contribute substantially to malaria pathogenesis. Indoleamine 2,3-dioxygenase (IDO) mediates the catabolism of tryptophan (TRP) into kynurenine (KYN), an immunosuppressive metabolite implicated in immune tolerance. This study aimed to investigate the role of TRP catabolism and regulatory T cells (Tregs) during P. vivax infection.MethodsPeripheral blood mononuclear cells (PBMCs) were stimulated in vitro with P. vivax-infected erythrocyte (Pv-iE) lysate to assess IDO-1 expression, KYN/TRP ratio, cytokine production, and Treg frequency. The effects of pharmacological inhibition of IDO, MyD88, and aryl hydrocarbon receptor (AhR) pathways were evaluated. Additionally, plasma KYN/TRP ratio, Treg frequencies, and cytokine levels were measured in patients with acute P. vivax infection and compared between individuals experiencing their first malaria episode and those with previous infections.ResultsStimulation with Pv-iE lysate increased IDO-1 expression in CD14+ cells, elevated KYN/TRP ratio, and induced pro-inflammatory cytokine production. IDO inhibition reduced KYN/TRP ratio and Treg frequencies upon Pv-iE stimulation. MyD88 inhibition decreased both IDO-1 expression and KYN/TRP ratio. IDO and AhR inhibition reduced Treg frequencies and CD4+ T cell proliferation. Patients with acute P. vivax malaria exhibited elevated KYN/TRP ratios and increased Treg frequencies, with a positive correlation between these parameters. Individuals with prior malaria episodes showed lower Treg frequencies, plasma IFN-γ, and KYN/TRP ratios compared to those with primary infections.DiscussionThese findings highlight the role of IDO-mediated TRP catabolism and innate immune signaling in promoting a tolerogenic phenotype during P. vivax infection. The study provides novel insights into mechanisms that may contribute to immune regulation, chronic inflammation, and tolerance during malaria, with potential implications for therapeutic interventions.